(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Social security for medical emergencies is not new to the Indian ethos. It is a common practice for villagers to take a ‘piruvu’ (a collection) to support a house- hold with a sick patient. However, health insurance, as we know it today, was introduced only in 1912 when the first Insurance Act was passed (Devadasan 2004). The current version of the Insurance Act was introduced in 1938. Since then there was little change till 1972 when the insurance industry was nationalized and 107 private insurance companies were brought under the umbrella of the General Insurance Corporation (GIC).